2014
DOI: 10.1080/08856257.2014.986905
|View full text |Cite
|
Sign up to set email alerts
|

The challenge for Deaf and hard-of-hearing students to learn foreign languages in special needs schools

Abstract: Deaf and hard-of-hearing (D/HH) learners have the right to equal access to knowledge and information which entails equal opportunities in learning foreign languages (FLs). As part of a larger project, the present study aims at exploring how students in eight specialised institutions across Hungary perceive the challenge of learning a FL. Following the principles of qualitative research, semistructured interviews were conducted with 31 14-19-year-old D/HH learners. A purposive sample aiming at maximum variety w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
15
0
7
Order By: Relevance
“…Previous studies on deaf and severely hard‐of‐hearing learners indicated the importance of teaching methods in shaping participants’ learning experiences as well as the fundamental role sign language use in and outside school plays in the participants’ lives and learning processes (Csizér, Piniel, & Kontráné Hegybíró, ; Kontra & Csizér, ; Kontra, Csizér, & Piniel, ); therefore, the following scales (using the same 5‐point format) were also included in our study: Teaching methods (4 items): what teaching methods and approaches are preferred in foreign language learning by deaf persons. Example: It would be nice if there were many Deaf English teachers . Beliefs about sign language in schools (5 items): the role participants attribute to the use of sign language in education.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on deaf and severely hard‐of‐hearing learners indicated the importance of teaching methods in shaping participants’ learning experiences as well as the fundamental role sign language use in and outside school plays in the participants’ lives and learning processes (Csizér, Piniel, & Kontráné Hegybíró, ; Kontra & Csizér, ; Kontra, Csizér, & Piniel, ); therefore, the following scales (using the same 5‐point format) were also included in our study: Teaching methods (4 items): what teaching methods and approaches are preferred in foreign language learning by deaf persons. Example: It would be nice if there were many Deaf English teachers . Beliefs about sign language in schools (5 items): the role participants attribute to the use of sign language in education.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 331 Deaf and hard-of-hearing adults revealed that, in the opinion of the investigated participants, positive learning experience is linked to sign language use in the classroom (Kontra & Csizér, 2013) as sign language is the easiest means of communication for Deaf persons. This view is reiterated in the first phase of the present investigation for Deaf and hard-ofhearing students, as Deaf learners think that intake, process and output is easier when information is conveyed through HSL (Kontra, Csizér, & Piniel, 2015). No previous Hungarian studies have systematically researched self and identity-related issues of Deaf and hard-of-hearing foreign language learners within a single theoretical framework.…”
Section: Self-related Motivational Researchmentioning
confidence: 99%
“…The investigation was designed to be a mixed-method and multi-perspective project including questionnaire and interview data from Deaf and hardof-hearing pupils studying in specialized schools around the country as well as interviews with their teachers and school-principals (Kontra, Csizér, & Piniel, 2015). The present article is the first publication that combines the results of the quantitative and qualitative student data.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos de los obstáculos contextualizados en las aulas en las que se imparte la materia de inglés como primera lengua extranjera están vinculados con el acceso a la información y a la comunicación, principalmente, debido a la utilización de la lengua oral, el peso que se le otorga como vehículo de transmisión de conocimientos e información y como código comunicativo para establecer interacciones con sus compañeros y profesores. A partir de esto, se debe acudir a los diversos sistemas para garantizar el acceso a la comunicación e información (Díaz-Estébanez & Valmaseda, 1995;Kontra et al, 2015), en el que deben contemplarse otros criterios didácticos y metodológicos, de necesaria aplicación durante la impartición de la asignatura de inglés, cuando se encuentre entre el alumnado estudiantes sordos y/o con hipoacusia. Domínguez y Alonso (2004) proponen como ejemplos de estos criterios los que se detallan a continuación: los principios que rijan la presencia de la Lengua de Signos Española (LSE) en la escuela y que se muestre el mismo estatus con respecto a las lenguas orales; asegurar la disponibilidad de los recursos tanto materiales como profesionales que son necesarios en la atención educativa para las personas sordas y la comprobación sistemática a la hora de garantizar una accesibilidad a la comunicación e información real en todos los ámbitos, lugares y momentos del centro educativo, entre otros.…”
Section: Necesidades Educativas De Las Personas Con Sordera E Hipoacusiaunclassified